The immediate and subsequent impact of a first-time traumatic anterior shoulder dislocation in people aged 16-40: Results from a national cohort study - Olds, M; Ellis, R; Parmar, P; Kersten, P (Shoulder & elbow, 2021)
Limited evidence exists which details changes in quality of life, shoulder activity level, kinesiophobia, shoulder pain and disability following a first-time traumatic anterior shoulder dislocation (FTASD) in people treated non-operatively. This study had three objectives: (1) to examine quality of life, pain, disability and kinesiophobia after an FTASD within 12 weeks, (2) to examine whether these variables were different in people with and without recurrent shoulder instability and (3) to assess how these variables changed over 12 months. A prospective cohort study was undertaken in people with an FTASD aged between 16 and 40 years. Measures of quality of life, kinesiophobia, shoulder activity, shoulder pain and disability were recorded within 12 weeks of an FTASD and at 3, 6, 9 and 12 months. An FTASD negatively impacted quality of life, shoulder pain and function and these variables improved over time. People with recurrent shoulder instability had poorer quality of life 12 months after an FTASD. Across the entire cohort, kinesiophobia did not significantly change across time in people following an FTASD. Quality of life was significantly affected by an FTASD in people with recurrent shoulder instability. Across the entire cohort of people with an FTASD, kinesiophobia remained elevated in people following an FTASD. Level 1 prognostic study.